Utilization of cyclohexanol by bacteria in a tropical estuarine water - Ilori, M O (Folia microbiologica, 1999)
The Lagos lagoon is a wide expanse of estuarine water. The range of temperature, pH and conductivity of samples collected from 3 sources were 27-30 degrees C, 7.8-8.3 and 2.34-2.85 mS respectively. Consistent increase and decrease in the population of indigenous bacteria occurred in the test and control experiments respectively. Organisms in samples from Apapa and Iddo utilized cyclohexanol better than those in the sample from the University of Lagos. The cyclohexanol degrading bacteria were identified as species of Pseudomonas. Acinetobacter, Vibrio, Micrococcus and Flavobacterium. Pseudomonas sp. had the highest growth potential on cyclohexanol. These organisms play important roles in reducing the pollutant loads of the Lagos lagoon.
Keywords: tropické klima; cyklohexanoly; Pseudomonas; chemické látky znečišťující vodu; Bacteria; Water Pollutants, Chemical; Biodegradation, Environmental; Cyclohexanols; Water Microbiology; Tropical Climate; mikrobiologie vody; biodegradace